MEDIA, DAKWAH, DAN TANGGUNG JAWAB SOSIAL: PERAN DA’I DALAM MEMBENTUK NARASI POSITIF - Gian Widayoko; khusnul khotimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Da'wah is an invitation to guide humanity towards a better path, following the guidance of Allah and His Messenger. It encompasses spiritual, social, moral, and ethical aspects. The purpose of da'wah is to improve interpersonal relationships, draw people closer to God, and provide understanding about a life filled with peace and happiness. Da'wah is not only intended for those who do not yet believe, but also for those who are already acquainted with religion but need a deeper understanding. Da'wah teaches values such as honesty, patience, humility, and compassion, and serves to strengthen human relations through harmonious and caring ways of life. The method used in this research is qualitative, with a literature study approach. The results of this study show that media-based da'wah, especially through social media, plays an important role in reaching a wider and more diverse audience amidst the challenges of globalization and digitalization. This media allows preachers (da’i) to transcend geographical and social boundaries, spreading messages in a more interactive and relevant way. However, media-based da'wah also faces challenges such as misinformation, social polarization, and misuse of information, requiring da’i to maintain credibility and carefully select content that aligns with Islamic teachings. Nevertheless, social media da'wah strengthens two-way interactions between da’i and the audience, creating spaces for discussion and enhancing religious understanding. With a wise approach and by maintaining the quality of the message, media-based da'wah can be an effective means to spread the peaceful, tolerant, and just values of Islam in the digital era. Keywords: Media; Da’wah; Social Responsibility; Da’i; Positive Narrative